Influence of Solution Annealing on Microstructure and Mechanical Properties of Maraging 300 Steel - Lima Filho, Venceslau Xavier de (2022)
Maraging 300 belongs to a family of metallic materials with extremely high mechanical strength and good toughness. Some works have been published about aging temperatures that improve ultimate strength resistance with acceptable toughness levels in this steel family, where the prior austenite grain size obtained by different solution annealing temperature influence in the final mechanical properties. Solution annealing temperatures ranging from 860 °C to 1150 ºC and were kept constant until the aging temperature. These treatments were used in order to investigate their influence on the microstructure and mechanical properties of maraging steel 300, especially with regard to toughness. The characterization of the microstructure was performed by optical microscopy, scanning electron microscope (SEM) and X-ray diffraction (XRD). Mechanical properties were evaluated by Rockwell C hardness and Charpy impact tests. The results showed that there is a temperature range where one can get some improvement in toughness without a large loss of mechanical strength.